Self-employment and labor market risks - Richard Audoly (Federal Reserve Bank of New York, 2024)
I study the labor market risks associated with being self-employed. I document that the self-employed are subject to larger earnings fluctuations than employees and that they frequently transition into unemployment. Given that the self-employed are not eligible to unemployment insurance, I analyze the provision of benefits targeted at these risks using a calibrated search model with (i) precautionary savings, (ii) work opportunities in paid and self-employment, and (iii) skill heterogeneity. This exercise suggests that extending the current U.S. unemployment insurance scheme to the self-employed comes with a clear increase in the transition rate from self-employment to unemployment and an unequal benefits-tocontributions ratio across skill groups. At the calibrated parameters, the self-employed in the middle of the skill distribution lose welfare.
Keywords: J40; J64; J65; 330; self-employment; unemployment insurance; earnings dynamics